The Impact of Ultramarathon Running on Acute Kidney Injury Risk - a Review od Current Evidence - Kluz , Agnieszka; Żak, Katarzyna; Jucha, Hubert; Mazur, Michał; Pliszka, Aleksandra; Michalak, Katarzyna; Zukierski, Krystian; Madyniak, Katarzyna (Quality in Sport, 2025)
Introduction and purpose Ultramarathon running has gained popularity in recent years, yet it presents unique physiological challenges. One of the increasingly recognized complications is acute kidney injury (AKI), which may result from extreme exertion. This review aims to summarize current knowledge on AKI risk in ultrarunners and identify key contributing factors. Material and method A narrative review of literature was conducted using PubMed, Scopus and Google Scholar databases. Keywords included: "ultramarathon", "acute kidney injury", "rhabdomyolysis", "NSAIDs", and "hydration". Peer-reviewed articles from 2000 to 2024 were included. Studies were selected based on their relevance to AKI mechanisms and prevalence in endurance athletes. Data were synthesized qualitatively. Results AKI in ultramarathon runners is multifactorial. Key contributors include dehydration, exercise-associated hyponatremia (EAH), exertional rhabdomyolysis, NSAID use, and gastrointestinal disorders impairing hydration and nutrition. While transient renal dysfunction is relatively common, severe AKI requiring intervention is rare. Biomarkers such as cystatin C and NGAL may provide more accurate diagnosis than creatinine alone. NSAIDs and EAH increase the risk of coexisting rhabdomyolysis, complicating clinical management. Conclusions Although the long-term health benefits of ultrarunning may outweigh the risks, AKI remains a clinically relevant concern. Medical supervision, adequate hydration strategies, and education on NSAID use are essential to reduce kidney-related complications in ultra-endurance athletes.